Criminal Law Policy in the Harmonization of Tax Regulations: Its Implications for State Income from the Tax Sector - Yoserwan, Yoserwan; Arma, Diana (Nagari Law Review, 2023)
Criminal acts in the field of taxation are a form of crime that is very detrimental to the state because they hinder state income from the tax sector. Taxes are the primary source of state income, which is then used for state management and in implementing development to improve community welfare. One effort to minimize criminal acts is to create regulations that become the basis for law enforcement for tax obligations. Overcoming criminal acts requires a criminal law policy that supports law enforcement. Criminal law outlines criminal policy, either substantive or procedural criminal law. The formulation of criminal law policy in tax laws is in line with the formation of tax law through the tax reform policy, which began in 1986 through the formation of several laws in the field of taxation. Finally, the Law Number 7 of 2021 concerning the Harmonization of Tax Regulations continues the policy. With the implementation of the Law on Harmonization of Tax Regulations, there needs to be a more in-depth study of tax criminal policies in this law towards optimizing state revenues from the tax sector. The research was conducted using normative legal research methods and supported by primary data. The approach used is a statutory approach, namely by analyzing various related laws in studying legal synchronization both vertically and horizontally and using legal theories. The research finds that criminal law policy in the Law on Harmonization of Tax Regulations applies more non-penal than penal policy. Non-penal prioritizes administrative settlement rather than criminal law settlement. The administrative settlement will enable more income through administrative fines. However, this approach does not fully support optimizing state revenues from the tax sector in the long run because this policy would not support taxpayer compliance.